Political culture of the migrant slum-dwellers in Calcutta - Chaudhuri Subrata (Calcutta Standard Book, 2005)
It seeks to fucus the nature and level of the political culture of migrant slum-dwellers in Calcutta. The introductory chapter deals with the research design. In the second chapter the origin and growth of Calcutta in the context of the influx of migrants
Keywords: Calcutta; Political culture; Slum-dwellers